2022
DOI: 10.1039/d2sc00855f
|View full text |Cite
|
Sign up to set email alerts
|

The Janus face of high trans-effect carbenes in olefin metathesis: gateway to both productivity and decomposition

Abstract: Ruthenium–cyclic(alkyl)(amino)carbene (CAAC) catalysts, used at ppm levels, can enable dramatically higher productivities in olefin metathesis than their N-heterocyclic carbene (NHC) predecessors. A key reason is the reduced susceptibility of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 104 publications
0
24
0
Order By: Relevance
“…Metathesis Catalysts and Carbene Ligands Discussed 29,34,43 In short, differences between the Hoveyda and Grela platforms are considerably smaller than differences resulting from the nature of the carbene. Although a steric contribution to the latter cannot be ruled out, we suggest that the dominant effect is the greatly increased trans effect/trans influence of the CAAC ligand, 24,26 a consequence of its stronger σ-donor and πacceptor properties. 14 We recently demonstrated that the high trans influence of the CAAC ligand plays a pivotal role in the decomposition of Ru−CAAC metathesis catalysts.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Metathesis Catalysts and Carbene Ligands Discussed 29,34,43 In short, differences between the Hoveyda and Grela platforms are considerably smaller than differences resulting from the nature of the carbene. Although a steric contribution to the latter cannot be ruled out, we suggest that the dominant effect is the greatly increased trans effect/trans influence of the CAAC ligand, 24,26 a consequence of its stronger σ-donor and πacceptor properties. 14 We recently demonstrated that the high trans influence of the CAAC ligand plays a pivotal role in the decomposition of Ru−CAAC metathesis catalysts.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…The greater stability of TS1-2 and 2 for HC1 Ph is expected from the stronger trans influence/trans effect of the CAAC ligand noted above. 24,26 Coordination of tBuVE to form π-complex 3 or 3′ (in which the alkene is oriented essentially parallel or orthogonal, respectively, to the Ru�C bond) is strongly endergonic, owing to steric repulsion between the carbene ligand and the alkylidene and alkene moieties. Repulsion will be stronger in the NHC system, as judged from the shorter carbene−alkylidene/ alkene distances in the π-complex of HII vs HC1 Ph (Figure S22), and the preceding transition states TS2-3 and TS2-3′.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No propenes ( 6a−c , Figure a) were detected for the CAAC catalyst nGC1 Ph in these experiments. In earlier studies conducted under anhydrous conditions, we reported that the CAAC catalysts, exceptionally, resist β-H elimination, because the high trans-influence of the carbene destabilizes the transition state for decomposition . The absence of propenes for nGC1 Ph indicates that water is unable to overcome this resistance.…”
mentioning
confidence: 99%
“…In earlier studies conducted under anhydrous conditions, we reported that the CAAC catalysts, exceptionally, resist β-H elimination, 38 because the high trans-influence of the carbene destabilizes the transition state for decomposition. 39 The absence of propenes for nGC1 Ph indicates that water is unable to overcome this resistance. In contrast, the yields of 6a – c for the NHC catalysts increase in the presence of water, as indicated by the other data in Figure 2 a. Hydrogen-bonding interactions between bound water and H β (see B′ ) are proposed to aid in the H-transfer step.…”
mentioning
confidence: 99%